RNA–protein interaction detection in living cells - Ramanathan, Muthukumar (Nat Methods, 2018)
RNA–protein interactions play numerous roles in cellular function and disease. Here we describe RNA–protein interaction detection (RaPID), which uses proximity-dependent protein labeling, based on the BirA* biotin ligase, to rapidly identify the proteins that bind RNA sequences of interest in living cells. RaPID displays utility in multiple applications, including in evaluating protein binding to mutant RNA motifs in human genetic disorders, in uncovering potential post-transcriptional networks in breast cancer, and in discovering essential host proteins that interact with Zika virus RNA. To improve the BirA*-labeling component of RaPID, moreover, a new mutant BirA* was engineered from Bacillus subtilis, termed BASU, that enables >1,000-fold faster kinetics and >30-fold increased signal-to-noise ratio over the prior standard Escherichia coli BirA*, thereby enabling direct study of RNA–protein interactions in living cells on a timescale as short as 1 min.